PENINGKATAN HASIL BELAJAR PENJUMLAHAN BILANGAN BULAT DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME DI KELAS V SD - Maret, Marsal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research was a class action that aims to improve learning outcome integers summings by the method of constructivist in class V 13 Surau Gadang elementary school. The subject were students of class V and teacher as observers. Action implementation procedures conducted in two cycle. Every cycle do the panning, implementation, observation, and reflection. Research conducted using qualitative and quantitative approaches. Based on the research result of cognitive test, affective, and psokomotor cycle 1 average 73,76 students, and increase in cycle II average student score 82,68. From the results of the study can be knowed, is a costructivist can improve the learning outcomes integers summings of students in the class V 13 Surau Gadang Padang elementary school. Kata Kunci : penjumlahan bilangan bulat, pendekatan konstruktivisme, siswa sd